Study of fracture mechanics in testing interfacial fracture of solder joints - Bang, W. H.; Moon, M. -W.; Kim, C. -U.; Kang, S. H.; Jung, J. P.; Oh, K. H. (SPRINGER, 2008)
This paper is concerned with the mechanics of interfacial fracture that are active in two common testing configurations of solder joint reliability. Utilizing eutectic Pb-Sn/Cu as a reference system and assuming the presence of a predefined crack size in the intermetallic compound (IMC) layer, stress intensity factors (K-I and K-II) at the crack are numerically calculated for the two given configurations. The analysis of the tensile test configuration reveals that the fracture occurs by the crack-opening mode (K-I mode), as anticipated, but that it is greatly assisted by the viscoplasticity of the solder. With nonuniform viscoplastic deformation across the joint, K-I is found to increase much more rapidly than it would without the solder, decreasing the critical crack size to the micron scale. The same mechanism is also responsible for the development of a K-II comparable to K-I at the crack tip, that is, vertical bar K-I /K-II vertical bar similar to 1. It is also found that the predominant fracture mode in the bump shear configuration is crack opening, not crack shearing. This is an unexpected result, but numerical analyses as well as experimental observations provide consistent indications that fracture occurs by crack opening. During shear testing, bump rotation due to nonzero rotational moment in the test configuration is found to be responsible for the change in the fracture mode because the rotation makes K-I become dominant over K-II. With rotational moment being affected by the geometry of the bump, it is further found that the fracture behavior may vary with bump size or shape.
Keywords: CU; BEHAVIOR; GROWTH